Probing Substituents in the 1- and 3-Position: Tetrahydropyrazino-Annelated Water-Soluble Xanthine Derivatives as Multi-Target Drugs With Potent Adenosine Receptor Antagonistic Activity - Koch, Pierre; Brunschweiger, Andreas; Namasivayam, Vigneshwaran; Ullrich, Stefan; Maruca, Annalisa; Lazzaretto, Beatrice; Küppers, Petra; Hinz, Sonja; Hockemeyer, Jörg; Wiese, Michael; Heer, Jag; Alcaro, Stefano; et al. (Frontiers in Chemistry, 2018)
Tetrahydropyrazino-annelated theophylline (1,3-dimethylxanthine) derivatives have previously been shown to display increased water-solubility as compared to the parent xanthines due to their basic character. In the present study, we modified this promising scaffold by replacing the 1,3-dimethyl residues by a variety of alkyl groups including combinations of different substituents in both positions. Substituted benzyl or phenethyl residues were attached to the N8 of the resulting 1,3-dialkyl-tetrahydropyrazino[2.1-f]purinediones with the aim to obtain multi-target drugs that block human A1 and A2A adenosine receptors (ARs) and monoaminoxidase B (MAO-B). 1,3-Diethyl-substituted derivatives showed high affinity for A1 ARs, e.g. 15d (PSB-18339, 8-m-bromobenzyl-substituted) displayed a Ki value of 13.6 nM combined with high selectivity. 1-Ethyl-3-propargyl-substituted derivatives exhibited increased A2A AR affinity. The 8-phenethyl derivative 20h was selective for the A2A AR (Ki 149 nM), while the corresponding 8-benzyl-substituted compound 20e (PSB-1869) blocked A1 and A2A ARs with equal potency (Ki A1, 180 nM; A2A, 282 nM). The 1-ethyl-3-methyl-substituted derivative 16a (PSB-18405) bearing a m,p-dichlorobenzyl residue at N8 blocked all three targets, A1 ARs (Ki 396 nM), A2A ARs (Ki 1,620 nM) and MAO-B (IC50 106 nM) with high selectivity versus the other subtypes (A2B and A3 ARs, MAO-A), and can thus be considered as a multi-target drug. Our findings were rationalized by molecular docking studies based on previously published X-ray structures of the protein targets. The new drugs have potential for the treatment of neurodegenerative diseases, in particular Parkinson’s disease.